2018
DOI: 10.1136/bmjsem-2017-000286
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standing postural control and gait parameters in people with and without chronic low back pain: a cross-sectional case–control study

Abstract: ObjectiveDifferences in postural control and gait have been identified between people with and without chronic low back pain (CLBP); however, many previous studies present data from small samples, or have used methodologies with questionable reliability. This study, employing robust methodology, hypothesised that there would be a difference in postural control, and spatiotemporal parameters of gait in people with CLBP compared with asymptomatic individuals.MethodsThis cross-sectional case–control study age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…Our results showed longer RT at the affected side of SIJD individuals that is in line with LBP studies (12,20,44,45) in which a longer RT was shown in LBP individuals. However, the present study was contrary to Macrae et al (46). The reason for this difference was due to methodological variations in other studies (12).…”
Section: Before Interventioncontrasting
confidence: 92%
“…Our results showed longer RT at the affected side of SIJD individuals that is in line with LBP studies (12,20,44,45) in which a longer RT was shown in LBP individuals. However, the present study was contrary to Macrae et al (46). The reason for this difference was due to methodological variations in other studies (12).…”
Section: Before Interventioncontrasting
confidence: 92%
“…Five studies reported kinetic measures in the lower extremities during walking[83,85,86,93,94]. In three studies examining sagittal plane total net joint moments at the hip, there were no differences between individuals with and without LBP[83,86,93]. During running, sagittal plane hip moments did not differ between groups[30,35].…”
Section: Resultsmentioning
confidence: 99%
“…Various options are available for assessment, such as the Sorenson test, 31 Prone Plank test, 32 Functional Movement Screen, 33 other movement control tests, 34 and laboratory-based gait analyses. 35 The Lumbar Spine Instability Questionnaire is a 15-item questionnaire that may be useful in assessing instability and guiding treatment approaches. 36,37 A thorough kinematic evaluation of bilateral lumbopelvic movement symmetry can provide important information for the management of patients with LBP.…”
Section: Kinematics Gait Motor Control and Muscular Functionmentioning
confidence: 99%
“…Successful management of lumbopelvic pain syndromes should include both anatomical and functional assessments of strength, endurance, flexibility, motor control, gait, and lumbopelvic kinematics. Various options are available for assessment, such as the Sorenson test, Prone Plank test, Functional Movement Screen, other movement control tests, and laboratory‐based gait analyses . The Lumbar Spine Instability Questionnaire is a 15‐item questionnaire that may be useful in assessing instability and guiding treatment approaches .…”
Section: Clinical Presentation and Assessment Of The Hypermobile Jointmentioning
confidence: 99%